Comparison of predicted settlement behaviour to the field measurement of stone column improved ground - Raman, Selvem (2006)
Stone columns form one of the accepted methods of ground improvement at which large size columns of coarse stones are installed into the ground by means of special vibrators. It is found that, stone columns increase shear strength of the ground, thus increasing bearing capacity and stability of the ground as well as to reduce settlement. The stone column design using Priebe’s method has gained much widespread use due to its simplicity. However it was found that the settlement computed using Priebe’s method has always been higher than the field settlement obtained. A comparison study was carried out between design settlement and field settlement. Based on the comparison and back analysis it is found that the improvement ratio of stone column increases with the increase of soil strength. This inherently implies to that of larger corresponding stone column spacing. Based on the findings, charts has been made to obtain a settlement reduction factor to be used in calculating the settlement of the improved ground, resulting in increase in the spacing and reducing the number of stone columns utilised. The time rate settlement was back calculated using Asaoka’s method to assess actual coefficient of vertical and horizontal consolidation. With this, the back calculated spacing together with the coefficient of consolidation parameters were used to simulate back the field settlement to validify the findings. Based on the simulation, it was found that the back calculated improvement ratio and spacing are corresponding well with the actual field settlement. Therefore a relationship was established for basic soil parameters and the parameters related to stone column settlement details.